Electoral reform and voter participation : Federal registration; a false remedy for voter apathy - Phillips, Kevin P.; Blackman, Paul H. (Washington, D.C. : American Enterprise Institute for Public Policy Research; Stanford, California : Hoover Institution on War, Revolution and Peace, 1975)
This volume assesses the importance of various factors affecting it, and review proposals for "some version of federal voter registration. It examines the law and practice of registering voters in various states of the union, the United States in earlier periods, and in Canada, Great Britain, Finland, Sweden, West Germany, and Australia.
Includes bibliographical references: p. 129-135.
lje 24/01/2019
Loans
Keywords: Voter registration; Voting